Effect of gypsum content on unsaturated engineering properties of clayey soil - N J Alzaidy, Mohammed (International Journal of Engineering and Technology, 2020)
Many of gypsum soils have existed in arid and semi-arid lands. It is considered one of the most problematic soils because of its complicated and unpredicted behavior when exposure to moisture. Extensive researches have been conducted in Iraq to observe the behavior of such soil and to suggest safety restrictions for the collapse and set practical precautions for the structures. This study investigated the effect of gypsum content on some unsaturated engineering properties of a clayey soil. Three different proportions of gypsum (0%, 5% and 20% by weight of the parent soil) were added and tested. The samples have been subjected to swelling potential test, soil water retention curve (SWRC), vapour diffusion and shear strength parameters. It is observed that gypsum content has a significant influence on SWRC, whereas, soil that has high gypsum content made SWRC with higher variables represented by air entry values and residual state. On the other hand, an increase in gypsum content led to a reduction of swelling potential and shear strength parameters. The results of vapour diffusion indicate that gypsum content could modify the microstructure in an unsaturated state and reduce the vapour diffusion through the soil.Â Â